A fresh look on economic evolution from kinetic viewpoint - Marco Lehmann-Waffenschmidt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
The present paper makes a contribution to fill in a gap left open by dynamic theory and evolutionary economics as well. While the "closed loop" dynamic theory has explanation power in analyzing evolving economic systems at the price of neglecting the possible occurrence of non anticipated novelties, "open loop" evolutionary economics is subject to the converse trade-off. Basing on a general equilibrium model by T. Kehoe including production and taxes we provide a formal model of an evolving economy fully accounting for the appearance of novelty. From this emerges in a natural way the notion of an open loop evolution equilibrium. It is based on arguments from the gradual vs. bang-bang tax reform controversy and from the debate on optimal macroeconomic policy design. Existence of equilibrium is established extending an analytical result which in a different context and independently has been proved by Mas- Colell and by the author. We use the term "kinetic" to indicate that in contrast to traditional comparative statics our approach neither hinges on the uniqueness of equilibria, nor is it confined to the analysis of prescribed parameter variations.
Keywords: B52; C62; D50; D58; 330; evolution; equilibrium; equilibrium price path; frictionless tuning of control parameters; Evolutionsökonomik; Dynamisches Gleichgewicht; Allgemeines Gleichgewicht; Theorie